Climate Factors with the Incidence of Dengue Hemorrhagic Fever in Semarang, Indonesia - Cahyati, Widya Hary; Marpid, Adrin Daila; Nugroho, Efa; Suharyo, Suharyo (Jurnal Kesehatan Masyarakat, 2024)
In Indonesia, Dengue Hemorrhagic Fever (DHF) remains a public health issue that can lead to extraordinary events. Indonesia ranks fourth in the world for the highest incidence of DHF. This is evident from the fluctuating morbidity and mortality rates due to DHF in Indonesia, including in Semarang. The purpose of this study is to determine the relationship between climatic factors and the incidence of DHF in Semarang from 2018 to 2022. This type of research is descriptive observational with an ecological study design. The data sources for the study are secondary data from the Semarang City Health Office and the Semarang City Meteorology, Climatology, and Geophysics Agency (BMKG) from 2018 to 2022. Data analysis was conducted using the Spearman Rank test. The results showed that rainfall (p= 0,004; r= 0,37), air humidity (p= 0,0001; r= 0,47), temperature (p= 0,016; r= -0,31), wind speed (p= 0,0001; r= -0,48), and duration of sunshine (p= 0,015; r= -0,31) were associated with the incidence of DHF. The conclusion of this study indicates that there is a correlation between climatic factors, such as rainfall, air humidity, temperature, wind speed, and duration of sunshine with the incidence of DHF in Semarang from 2018 to 2022.